2013
DOI: 10.1007/s00436-013-3655-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles shed by Trypanosoma cruzi are linked to small RNA pathways, life cycle regulation, and susceptibility to infection of mammalian cells

Abstract: The protozoan parasite Trypanosoma cruzi has a complex life cycle characterized by intracellular and extracellular forms alternating between invertebrate and mammals. To cope with these changing environments, T. cruzi undergoes rapid changes in gene expression, which are achieved essentially at the posttranscriptional level. At present, expanding families of small RNAs are recognized as key players in novel forms of posttranscriptional gene regulation in most eukaryotes. However, T. cruzi lacks canonical small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 71 publications
6
151
0
Order By: Relevance
“…It is known that T. cruzi parasites, like many other cells, release extracellular vesicles that are postulated to be involved in cell-cell communication or in the modulation of the host immune responses to promote the establishment of an infection (26)(27)(28)(29). These vesicles typically consist of a lipid bilayer membrane containing integral membrane proteins and a luminal cavity that is loaded with a variety of soluble proteins and nucleic acids (RNA and DNA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that T. cruzi parasites, like many other cells, release extracellular vesicles that are postulated to be involved in cell-cell communication or in the modulation of the host immune responses to promote the establishment of an infection (26)(27)(28)(29). These vesicles typically consist of a lipid bilayer membrane containing integral membrane proteins and a luminal cavity that is loaded with a variety of soluble proteins and nucleic acids (RNA and DNA).…”
mentioning
confidence: 99%
“…These include exovesicles (EVs; also referred to as ectosomes; 100 to 1,000 nm), which bud directly from the plasma membrane, and exosomes (30 to 100 nm), which are vesicles that are secreted into the extracellular environment following the fusion of multivesicular endosomes with the plasma membrane, typically occurring at the flagellar pocket membrane (28,(30)(31)(32)(33). A proteomic analysis of extracellular vesicles released by metacyclic trypomastigotes and epimastigotes in culture demonstrated the presence of two populations of EVs containing plasma membrane and intracellular proteins, and also nucleic acids (26,29,(32)(33)(34). Interestingly, treatment of mice with EVs shed by axenic trypomastigotes caused a downmodulation of the host immune response that was associated with higher parasitemia and an exacerbated inflammatory response that resulted in increased mortality following infection (26,35).…”
mentioning
confidence: 99%
“…Furthermore, parasites transfected with Cy3-labelled tsRNAs are able to transfer these to other parasites and to mammalian cells [42]. Reprogramming of host cell expression cannot be attributed to these alone, however; transfection of HeLa cells with individual tsRNAs resulted in many fewer changes in transcript levels and, for the most part, these were not concordant with the results obtained with vesicles [41].…”
Section: Parasite-derived Vesicles For Long-range Communication With mentioning
confidence: 80%
“…This was most apparent 6-24 hours post exposure, with most transcripts returning to basal levels after 72 h [41]. The RNA contents of the extracellular vesicles shed by T. cruzi are mainly derived from rRNAs and a restricted subset of tRNA fragments (tsRNAs) [42].…”
Section: Parasite-derived Vesicles For Long-range Communication With mentioning
confidence: 99%
“…This organelle is involved in the accumulation of both macromolecules ingested through the endocytic pathway as well as some proteases, especially cruzipain, that is synthesized by the parasite [50]. It was subsequently shown that tsRNAs were localized in organelles associated with clathrin and with the T. cruzi argonate protein TcPIWI-tryp that is morphologically characterized as reservosomes as well as in uncharacterized cytoplasmic vesicles and in Golgi-like vesicles [51]. It was also shown that 20-200 nm vesicles are released from the parasites into the extracellular medium from reservosome-like structures containing vesicles that touch the cytoplasmic face of the plasma membrane.…”
Section: Exosomes In the Protozoan Trypanosoma Cruzimentioning
confidence: 99%